The Impact Of Marketing Monitoring On Performance - Moussaoui, Kahina; Benabdeslam ,Chafiaa; Djemah ,Nouara (University of Eloued جامعة الوادي, 2025)
Companies are finding it very challenging to develop offerings and sustain competitive advantage in a market that is becoming increasingly competitive and where customers are growing more savvy and discerning. This underscores how vital it is for companies to understand the changing dynamics, patterns, and behaviors of key actors in their context. These problems can be solved using tactics such as marketing surveillance, environmental surveillance, and business intelligence. This study was motivated by the challenge to investigate how marketing monitoring affects business performance. We used a sample of Algerian exporting companies to accomplish this, and SmartPLS was used to analyze the collected data. We discover that marketing monitoring improves overall business success.
The Impact of Marketing Monitoring on Performance. Case of Algerian exporting companies.
مقال
Keywords: Marketing monitoring; Strategic information; Organizational performance; Exporting companies; Algeria.